Gambaran Asupan Zat Gizi Makro dan Status Gizi Remaja SMA di Kota Surakarta - Anggun Oktavia Widiastuti; Endang Nur Widyaningsih (HB PRESS, 2023)
Food intake is a direct factor that can affect the nutritional status of adolescents. Imbalance of food intake will cause nutritional problems in adolescents. The survey results from two senior high schools showed that 16.46% of adolescents were overweight. This study aims to determine the description of macronutrient intake with nutritional status of high school adolescents in the city of Surakarta. This type of research uses observational research with a cross-sectional approach. The population in this study were teenagers in class XI and XII as many as 943 students. Sampling by simple random sampling method with a sample of 88 students. Food intake data was obtained by food recall 3x24 hours, namely 2 weekdays and 1 weekend with the method of 1 day direct interview and 2 days via whatsapp, food intake data was processed using NutriSurvei 2007 software. Nutritional status data was obtained based on anthropometric measurements, namely weight weighing using digital weight scales and measurement of height with microtoice, nutritional status assessment parameters using Body Mass Index according to Age (BMI/U). The results showed that most of the intake of carbohydrates (73.9%), fat (64.8%) and protein (52.3%) of adolescents were included in the category of weight deficit. As many as 14.8% of adolescents have abnormal nutritional status. Respondents with poor intake of protein, fat and carbohydrates showed more abnormal nutritional status. Adolescents must pay attention to the adequacy of fat intake so that it is balanced with daily needs.